Pelanggaran Kesantunan Berbahasa pada Acara Rakyat Bersuara: Orang Besar di Balik Gaduh Ijazah Jokowi: Violation of Language Politeness at the People's Voice Event: The Big Man Behind the Jokowi Diploma Uproar - Suci Sri Wahyuni; Andiopenta Purba; Deri Rachmad Pratama; Akhyaruddin Akhyaruddin (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to describe the forms of language politeness violations found in the Rakyat Bersuara program entitled "The Big Man Behind the Noise of Jokowi's Diploma." This study uses a pragmatic approach with a descriptive qualitative research type. The data for this study are speeches containing violations of language politeness. The data source for this study is the Rakyat Bersuara program, July 30, 2025 edition, entitled "The Big Man Behind the Noise of Jokowi's Diploma" on the INEWS YouTube channel. The data collection technique in this study uses the listening and note-taking method. Data validity is checked using the theory and method triangulation technique. This study uses Leech's (1993) politeness theory as the basis for analysis. The data analysis technique in this study uses the Miles and Huberman interactive model which includes three stages: data reduction, data presentation, and conclusion drawing. The results of the study showed that there were violations of politeness in six maxims, namely 2 violations of the maxim of wisdom, 1 violation of the maxim of generosity, 5 violations of the maxim of praise, 1 violation of the maxim of humility, 1 violation of the maxim of agreement, and 2 violations of the maxim of sympathy. Violations of politeness in language were used to defend arguments, to attack interlocutors who disagreed, and also to enhance one's positive image and to maximize losses to interlocutors.